Do tropical rain forest soils have greater nematode diversity than high arctic tundra? a metagenetic comparison of Malaysia and Svalbard - Kerfahi, Dorsaf; Tripathi, Binu M.; Porazinska, Dorota L.; Park, Jungok; Go, Rusea; Adams, Jonathan M. (Wiley, 2016)
Aim Latitudinal differences in diversity have long fascinated ecologists. It is unclear whether small soil animals such as nematodes show latitudinal differences in diversity. Based on hypotheses concerning the basis for greater tropical diversity, and by analogy with other groups, we predicted (1) greater alpha diversity in the equatorial tropics than the High Arctic, (2) greater beta and gamma diversity in the tropics. We also predicted (3) no species overlap between the tropics and the High Arctic, and (4) lower abundance of root feeding and insect parasitic nematodes in the high Arctic.